Penilaian Sikap Pada Country Of Origin Image Terhadap Sustainability Dan Evaluasi Produk - Prakosa, Adhi (Akmenika, 2016)
Nowadays, marketers are faced with a higher level of consumers concern on socialand environmental issues. Due to that reason, it is important for marketers to assesstheir business practices related to the country of origin products and concern ofcompany on issue of environmental sustainability. The aim of this study is to examinedifferences in response of consumers towards attributes of environmental sustainabilityand product evaluation visits of their attitudes towards country of originimage. The dependent variable in this research is consumer perceptions on corporatesocial responsibility, transparency, and trust, where as the attitude of countryof origin is the independent variable. The survey method is used in this study toevaluate hypothesis using one-way ANOVA analysis. As the result, it can be concludedthat confidence of consumer in the company and the evaluation of the productwill be different between consumers who have a high and a low country of originimage.